A Rare Case of Empyema Developed after Transarterial Chemoembolization for Hepatocellular Carcinoma - Young Keun Sur (대한영상의학회지, 2015)
A 60-year-old male patient who previously underwent transarterial chemoembolization for recurrent hepatocellular carcinoma three months ago presented to the emergency department with pleural effusion and hemoptysis. On serial review of plain radiographs and chest CT, transdiaphragmatic migration of Lipiodol from the treated area of the liver into the ipsilateral pleural cavity was demonstrated. The patient consequently developed empyema in the right thorax. Therefore, percutaneous drainage was performed. Empyema and pleural effusion regressed after 10 days of medical treatment and drainage. After that, the patient was transferred back to the local clinic upon full symptomatic recovery. Herein, we describe a rare complication of transarterial chemoembolization for hepatocellular carcinoma manifesting as an empyema secondary to the migration of the ethiodized oil content from the liver into the ipsilateral pleural cavity.